2014
DOI: 10.1002/pc.23113
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaved aerated concrete waste (AACW): An alternative filler material for the natural rubber industry

Abstract: Material waste from the production of autoclaved aerated concrete, a porous material, should be considered as a valuable byproduct for use as a filler material for the rubber industry. Natural rubber (NR) composites filled with different loading (over the range of 0-60 phr) of autoclaved aerated concrete waste (AACW) as a new eco-friendly material were produced using two roll mills and then were studied for their cure characteristics, mechanical and aging properties, and morphology, and also compared with comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, in the case of raw material powder passed with 100 mm sieve, it was reported that quantity required to experiment was difficult to prepare and it takes time to be milled. For composite material using waste concrete powder, the mortar, 14 cementitious composite, 15 polymer composite 49,50 and natural rubber composite 51 have been reported. These waste concrete powders were prepared by dust collection system of demolish structure or mechanical grinding, and they have not been classed for recycled coarse aggregate and recycled fine aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of raw material powder passed with 100 mm sieve, it was reported that quantity required to experiment was difficult to prepare and it takes time to be milled. For composite material using waste concrete powder, the mortar, 14 cementitious composite, 15 polymer composite 49,50 and natural rubber composite 51 have been reported. These waste concrete powders were prepared by dust collection system of demolish structure or mechanical grinding, and they have not been classed for recycled coarse aggregate and recycled fine aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SiO 2 , another stable chemical, was added to rubber materials to significantly reduce the rolling resistance of vulcanized rubber, and improve the resistance to wet, flexural, and tensile strength and other properties of SiO 2 . [20][21][22][23][24] The results show that the combination of SiO 2 and carbon black can significantly improve the problem of high rolling resistance of carbon black, and achieve the reduction of rolling resistance while having a certain anti-slippery performance. [25][26][27] Song et al [28] proposed a model to illustrate its vulcanization characteristics of carbon black and SiO 2 filler network structure, cross-linking density, binding glue content, and other properties.…”
Section: Introductionmentioning
confidence: 99%